Educational and skill development needs of early-career rheumatologists in Türkiye - Mert Öztaş; Gizem Ayan; Emre Bilgin; Ertuğrul Çağrı Bölek; Ufuk İlgen (Ulusal Romatoloji Dergisi)
Objective: Several previous reports from Europe have disclosed the educational needs of early-career rheumatologists on an international scale. We aimed to identify and characterize the current clinical and academic educational needs of early-career rheumatologists in Türkiye. Methods: This cross-sectional study was conducted via an online survey distributed to rheumatology fellows in training and consultants working in Türkiye. The survey, distributed by SurveyMonkey, was sent to all Turkish Society of Rheumatology (TSR) member trainees and consultants. The questionnaire included sections on demographics, current professional status, academic interests, and awareness of various TSR programs. Clinical and academic domains were assessed separately using a 7-point scale, with 1 indicating the highest need. Results: The survey was sent to all rheumatology trainees and consultants who are members of the TSR (n=190), and data from 113 participants (59.4%) were analyzed. Most of the respondents (68.1%) were rheumatology trainees, while the remaining were consultant rheumatologists. In the clinical domain, the most needed skill for both trainees (2.6±1.7) and consultants (2.9±1.8) was musculoskeletal ultrasonography. This was followed by X-ray interpretation among trainees (4±1.6) and magnetic resonance imaging interpretation (3.6±1.3) among consultants. In the academic domain, trainees primarily expressed a need for training in scientific writing (2.8±1.6), while consultants prioritized statistical education (2.7±1.4). Research methodology was the second most frequently requested topic in both groups. Awareness of the educational and academic opportunities provided by the TSR varied greatly among participants. Conclusion: Musculoskeletal ultrasound emerged as the most reported clinical skill need, emphasizing its relevance and the necessity of incorporating it into routine clinical practice. While the educational programs offered by the TSR are relatively well-known and widely attended, awareness and utilization of academic support mechanisms remain limited.